IMPLEMENTASI PELAKSANAAN BIMBINGAN DAN KONSELING TERHADAP PEMBENTUKAN KARAKTER SISWA SEKOLAH DASAR DI KECAMATAN KUTOARJO - Widyati, Septy (Jurnal Cerdik: Jurnal Pendidikan dan Pengajaran, 2023)
Personal guidance and counseling refers to the efforts given by the counselor to counseling so that the counseling can understand, accept, direct himself to be an optimal person. Many counseling problems experienced by students. Problems experienced due to lack of attention from parents, because they are busy working. Then students also experience difficulties in participating in teaching and learning activities in class, seniority. It can hinder child development. To deal with this problem, it is necessary to collaborate between class teachers and parents to provide guidance and counseling. Guidance. This counseling guidance includes, mental attitude, independence, direction in education. To develop the potential of students and help solve the problems they face. Purpose of Counseling Guidance. the purpose of guidance and counseling services is to try to help counselees to: a. Planning study completion activities, career development in the future, b. Develop all its potential and strengths, c. Adjusting to the educational environment, community environment and work environment, d. Overcoming obstacles and difficulties encountered in study, adjustment to the educational environment, society, and work environment Teachers must provide special handling and more attention to students who have difficulties in learning than students who do not experience difficulties in learning. By providing additional hours at the end of learning hours.Keyword: counseling guidance, problems, goals